2008
DOI: 10.1186/1472-684x-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement help-seeking following an 'expected' death: a cross-sectional randomised face-to-face population survey

Abstract: Background: This study examines the prevalence and nature of bereavement help-seeking among the population who experienced an "expected" death in the five years before their survey response. Such whole population data are not limited by identification through previous access to specific services nor practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…Although a few previous studies have examined mental health service use by the bereaved (1,2,7,8), research on individuals with prolonged grief disorder is limited. We observed that only 43% of caregivers who met criteria for prolonged grief disorder accessed mental health services, compared with 63% of those who met criteria for major depressive disorder, generalized anxiety disorder, posttraumatic stress disorder, or panic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few previous studies have examined mental health service use by the bereaved (1,2,7,8), research on individuals with prolonged grief disorder is limited. We observed that only 43% of caregivers who met criteria for prolonged grief disorder accessed mental health services, compared with 63% of those who met criteria for major depressive disorder, generalized anxiety disorder, posttraumatic stress disorder, or panic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Use of such services by bereaved individuals has ranged from as little as 2% to 30% (1,2,7), depending on the samples, the type of service used, and the relationship of individuals to the deceased. Mental health service use after bereavement may have enduring and broad positive effects, including the potential to counter adverse health consequences, such as premature mortality, that have been associated with the loss of a loved one (8).…”
mentioning
confidence: 99%
“…This represents a major barrier in this field. A recent Australian population-based study highlighted the potential health gains that could be obtained from focusing on the sub-group of bereaved people who wished they had sought help but did not [69].…”
Section: Limitations Of Studiesmentioning
confidence: 99%
“…Of particular concern is that bereavement support in palliative care tends to be offered to all bereaved persons, irrespective of need (8,10,11). However, research indicates that, within the bereaved population, those experiencing greater distress, do not seek help (10,(12)(13)(14). This provision of blanket bereavement support means that some bereaved caregivers, possibly those in greatest need, may be overlooked, while others receive support they do not need (14,15).…”
Section: Introductionmentioning
confidence: 99%